Robomind Utilization to Improve Student Motivation and Concept in Learning Programming - Yuana, Rosihan Ari; Maryono, Dwi (Proceeding of International Conference on Teacher Training and Education, 2016)
Robomind is one of the PAT (programming assistance tool) software that used as a tool for programming learningÂ and improving the understanding of programming concepts, as well as improving the ability of logical thinkingÂ and problem solving. The advantages of Robomind compared to the other PATs are a simple graphical displayÂ and attractive, it can be used for students ranging from primary schools, secondary schools and further education.Â Besides design and features, Robomind has also fulfilled the Robert Gagneâs instructional theory concept. Theaim of this study is how to utilize robomind as a tool to motivate students in learning computer programming andÂ know the students responses to its use in understanding the programming concepts. This research is motivated byÂ the lack of student motivation in learning programming that caused by the initial perception that programming isÂ difficult. In addition, some programming elusive concepts also make the lack of motivation to learnÂ programming. This research was conducted at the Department of ICT Education FKIP UNS on StructuredÂ Programming course in first semester. Results showed, there were 90% of students feel motivated to learnÂ programming although not previously been familiar with programming at all. In addition, it is also obtained from Â the survey that 20% of students who previously had studied programming, 85% of whom could have betterÂ understanding concepts that were previously less understood.